2020
DOI: 10.3390/diagnostics10030168
|View full text |Cite
|
Sign up to set email alerts
|

Triple Metachronous Malignancies with Thyroid Involvement: A Brief Overview of Five Case Reports over 20 Years of Institutional Experience

Abstract: Multiple primary malignant tumors are defined by the development of more than one malignancy in a single patient. These can be subdivided into synchronous or metachronous malignant tumors, depending on their time of appearance, relative to the first malignancy. Triple primary malignancies are a relatively rare occurrence in day-to-day practice and triple synchronous or metachronous carcinomas involving a thyroid localization are even less common. In this case series, we report our 20-year experience in diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Drug resistance was also observed in the study case, necessitating an alteration of the therapeutic regimen. The patient died 20 months after initiation of targeted drug therapy; the poor prognosis in this case was consistent with findings from previous studies ( 2 , 3 , 25 ), which reported poor outcomes in young female patients with MPCs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Drug resistance was also observed in the study case, necessitating an alteration of the therapeutic regimen. The patient died 20 months after initiation of targeted drug therapy; the poor prognosis in this case was consistent with findings from previous studies ( 2 , 3 , 25 ), which reported poor outcomes in young female patients with MPCs.…”
Section: Discussionsupporting
confidence: 91%
“…Warren proposed the following criteria for the diagnosis of MPCs ( 1 ): (1) every tumor must be malignant; (2) every tumor has to be confirmed histopathologically; (3) each tumor must occur at different sites and not be continuous with each other; and (4) the possibility of metastatic or recurrent tumors should be eliminated. MPCs are rarely found ( 2 , 3 ); the five most frequent sites include the breast, liver, head and neck, colorectum, and prostate ( 2 ). Unlike the five most frequent sites ( 2 , 3 ), which account for 3.1% of all MPC diagnoses ( 2 ), the thyroid is a rare site for their occurrence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synchronous cancer occurs when two tumors arise simultaneously or sequentially within a six-month period, whereas metachronous cancer involves tumors discovered consecutively with an interval exceeding six months. 1 …”
Section: Introductionmentioning
confidence: 99%
“…Billroth reported multiple primary neoplasms for the first time in 1889. Later, in 1932, Warren and Gate classified MPMTs into two different types [ 1 ]. Synchronous MPMT, where a malignancy arises from a different (origin) primary tumor that develops within six months from the original primary tumor, differs from metachronous MPMT where a different tumor from the (original) primary tumor develops in more than six months after the primary tumor [ 2 ].…”
Section: Introductionmentioning
confidence: 99%